Identifikasi Bakteri Clostridium Botulinum pada Buah Leci Kemasan Kaleng - Hardianti, Siti; Nasution, Masriani Hasyim (Riviera Publishing, 2025)
In Indonesia, the most popular canned foods include sardines and canned corned beef, while the most popular canned drinks are canned lychee fruit. Inadequate heating temperature and time during sterilisation can result in the growth of Clostridium botulinum bacteria. Clostridium botulinum in the human body causes a disease that can attack the nervous system called botulism. This disease occurs because the patient accidentally eats the toxin from Clostridium botulinum bacteria found in imperfectly preserved foods such as those found in canned foods. Clostridium botulinum in the human body causes a disease that can attack the nervous system called botulism. This disease occurs because the patient accidentally eats the toxin from Clostridium botulinum bacteria found in imperfectly preserved foods such as those found in canned foods. This study was to find and identify Clostridium botulinum bacteria that can be found in canned lychee fruit. The type of research used was descriptive univariate research used to find Clostridium botulinum on lychee fruit in canned packaging from various brands sold. showed that none of the lychee fruit samples were identified by Clostridium botulinum bacteria. From the study, it was found that Clostridium botulinum bacteria in canned lychee fruit marketed in supermarkets in Medan city were negative.